Financial Risk Assessment of Enterprise Management Accounting Based on Association Rule Algorithm under the Background of Big Data. (17th May 2022) - Lin, Yibin; Yue, Huabo; Liao, Haojie; Li, Dong; Chen, Ling
Abstract : Under the background of the rapid development of data informatization, the evaluation and analysis of enterprise management accounting risk are the key link of enterprise sustainable development. Based on the theoretical basis of enterprise management accounting risk analysis, this paper selects 11 representative corporate financial risk indicators from financial risk indicators through correlation analysis and then selects 8 key indicators that affect corporate financial risk through association rules, to assess and analyze the company's financial risks. Finally, this paper takes 20 ST companies in China as the research object to carry out empirical research. According to the assessment and analysis of financial risks in the company's management accounting, it proposes measures from four modules to strengthen the company's ability to resist risks.